Metode Penelitian Kepustakaan - James Danandjaja (Antropologi Indonesia, 1997)
Conducting a literature review is an important part of a research. This step is an endeavor to prevent duplication. The author discusses three steps to conduct library research which exemplified by his own experience. First, reviewing literature pertained to research problem. Second, data collecting technique through library research. Finally, he encourages social scientists to conduct library research and write annotated bibliography of certain topic of Indonesian culture.